The impact of outmigration on the socio-economic structure of a rural village in West Malaysia: Kampong Parit Changkat / Catherine Xavier - Catherine , Xavier (1981)
This report examines the impact of outmigration on the socio-economic structure of a rural village in West Malaysia, Kampong Parit Changkat situated in the Sabak Bernam District of upper Selangor. It represents an agricultural society with a subsistence based dual economy: (padi) rice cultivation, cocoa and coconut plantations. Chapter I provides basic information on the location of the village, the settlement pattern and a general over view of the socio-economic and political structure of the village. This is followed by an account of the aims and objectives of the study. The third part of the chapter deals with the type of methods used to extract data, participant observation, interview schedule and informal interview/conversations. Studies conducted by social scientist were also referred too. Chapter II provides a detailed account of the social and economic situation at the village level with emphasis on the role of the nuclear family-basic organizational cell. Village activities and household roles/activities are also dealt with in detail. The values and norms that dictate their daily lives is also examined. Chapter III deals with the impact of outmigration in the rural place of origin. The consequences of outmigration on the demographic level and the agricultural productivity, the impact of migrant remittances, the drain of rural income to urban areas, the change in occupational structure and the impact at the family level are examined. A review of the change in attitude towards city life is also dealts with. The concluding chapter sums up the totality of the impact of outmigration